Hubungan Status Vitamin D dengan Risiko Jatuh pada Pasien Lansia dengan Penyakit Ginjal Kronik yang Menjalani Hemodialisis Reguler - Iqbal, Muhammad; Ariestine, Dina Aprillia; Ramadhani, Sumi (Jurnal Penyakit Dalam Indonesia, 2023)
Introduction. Fall is one of the main causes of hospitalization in the elderly, which is caused by several factors including gait disturbances, balance disorders, visual disturbances, chronic kidney disease (CKD), vitamin D deficiency, and so on. Chronic kidney disease can cause disruption of vitamin D metabolism, especially in the elderly population. This study aimed to assess the relationship between vitamin D status and the risk of falling in elderly patients with CKD who receive regular hemodialysis programs. Methods. We conducted a cross-sectional study by assessing the relationship between vitamin D status and the risk of fall in elderly patients undergoing regular hemodialysis at H. Adam Malik General Hospital and Rasyida Kidney Special Hospital Medan. Fall risk assessment was carried out using the Morse fall scale (MFS) and vitamin D status was examined in the Clinical Pathology Laboratory of H. Adam Malik General Hospital, Medan. The data was analyzed statistically with the chi square test. Results. This study involved 92 subjects with a median vitamin D level of 20.15 (3.9-52.1) mg/dL and a median MFS value of 65 (25-95). As many as 87% of subjects had insufficient vitamin D levels, 11% of subjects had inadequate levels, and 1% of subjects had adequate levels of vitamin D. High fall risk was found in 56% of subjects, 43% had moderate fall risk, and 1% had low fall risk. The chi square test found a significant relationship between vitamin D status and risk of falling with p value = 0.001 and an odds ratio 0.056 (95%CI 0.007-0.454). Conclusion. Reduction of vitamin D level has a significant relationship with the risk of falling in elderly patients with CKD undergoing regular hemodialysis.